PENGARUH GAYA KEPEMIMPINAN DAN BEBAN KERJA TERHADAP STRES YANG DIRASAKAN OLEH KARYAWAN DAN DAMPAKNYA TERHADAP KINERJA KARYAWAN - R. Suyudi Muriawan; Tiar Sinaga (Jurnal Ilmu Keuangan dan Perbankan (JIKA), 2017)
The purpose of the study to determine the effect of leadership style, workload, work stress and employee performance employee either simultaneously or partially. The method of research used descriptive method of analysis with a quantitative approach that aims to describe in a systematic and factual account of the facts as well as the relationships between variables were investigated by means of collecting data, processing, analyzing, and interpreting data in a statistical hypothesis testing as well as the method of path analysis. Techniques of data collection through literature study and a questionnaire with the help of SPSS 19. The results showed leadership style can be quite good with low employee stress. Leadership style and workload influence on employee stress. Leadership style and workload influence on employee performance. While the partial effect of leadership style on employee performance. Workload affect the performance. Effect of work stress on employee performance and there is the influence of leadership style, workload, and stress felt by the employees and their impact on employee performance. Keywords: leadership style, workload, work stress and employee performance